Analisis Karakteristik Bahasa yang digunakan dalam Interaksi Sosial Anak Sekolah Dasar - Aulia Cantica Nur Elisa; Keisya Amalia Nabila; Silvina Noviyanti; Nazurty; Tya Ramadhani; Viska Agima putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the linguistic characteristics used in the social interactions of elementary school children and the factors influencing them within the school environment. Utilizing a library research method with a qualitative approach, this study synthesizes various academic sources from the last decade to map children's communication patterns. The results indicate that the linguistic characteristics of elementary students reflect a cognitive transition from egocentric to sociocentric behavior, where children begin to develop pragmatic skills and politeness strategies in social negotiation. Furthermore, a strong phenomenon of diglossia was found in certain regions, characterized by a functional separation between local languages as a symbol of solidarity and Indonesian as a formal educational medium. To overcome communication barriers, educators implement code-switching and code-mixing strategies to bridge student understanding. This study concludes that the language of elementary school children is a dynamic blend of cultural identity, digital media influence, and adaptation to social norms in the school setting. Keywords: Language Characteristics, Social Interaction, Elementary School Children, Pragmatics, Literature Study.